Factors affecting Malaysia household debt / Nurul Azira Zainal Bidin - Zainal Bidin, Nurul Azira (Faculty of Business and Management, 2018)
This study explores the factors that affect the household debt in Malaysia. This study is using quarterly data over the period January 2006 to December 2016 for the three independent variables which are Gross Domestic Product (GDP), Interest Rate (IR) and Unemployment Rate (UR). All data were collected from DataStream. This current study employs ordinary least square (OLS) in examining the factors affecting the household debt in Malaysia. The finding indicates that there is a positive significant relationship between gross domestic product and household debt. Meanwhile, it was discovered that there are negative significant relationship between interest rate and unemployment rate with household debt.